Control beliefs of teacher educators regarding their research engagement. Issue 4 (7th June 2022) - Nicholson, Laura J.; Lander, Vini
ABSTRACT: Strong evidence has emerged that teacher educators (TEs) should be directly and actively engaged in the research process. Despite this, relatively low levels of research activity have been observed. In 2014, the British Educational Research Association (BERA) called for a national strategy to embed research-informed practice into teacher education. Previous research has revealed that TEs encounter several barriers to engaging in research. This study aimed to provide a current and detailed account of perceptions of control and ability to engage in research in a sample of TEs based at a new university in England, using the framework of the theory of planned behaviour. Semi-structured interviews were conducted with 16 TEs to elicit control beliefs underlying research engagement. Beliefs mentioned by at least 25% of the sample were defined as accessible beliefs and were retained for further qualitative analysis. Interpretative phenomenological analysis revealed seven higher-order control factors that influenced the motivation to engage in research. Specifically, these comprised a lack of time, insufficient mentoring, limited opportunities for collaboration, the nature of initial teacher education, changes in the faculty, various feelings (mostly negative) and inflexible research procedures. These accessible beliefs can be targeted by faculties of education to increase research engagement. In future research we will collect quantitative data about these beliefs from a larger sample of TEs. Empirical relationships between the control beliefs and intention to engage in research and actual research engagement will be investigated, which will allow evidence-based interventions, rooted in the qualitative data, to be developed.